Disseminating Weed Management Technology for Changing Economic Scenario of Farmers - Singh, P K; Barman, K K; Singh, D.K. (Indian Journal of Extension Education, 2011)
Improved weed management techniques must be an important component of crop production strategies to cut down production cost. How the introduction of modern weed management techniques could change the adoption behaviour towards other farming technologies, and consequent economic benefit of the farmers have been reported in this paper. The study was conducted in an agricuturally backward village Tagar mahagawa under Panagar Block of Jabalpur district in Madhya Pradesh in the year 2008. Prior to adoption, rice-wheat system was the major cropping pattern of the village, and none of the farmers practiced commercial cultivation of vegetables and other cash crops due to severe weed problem. In general the farmers practiced manual weeding during kharif season and no weeding operation was practiced during rabi season. The action plan was initiated by conducting demonstrations for showing performance, practicability and profitability of improved weed management technologies to the villagers. The villagers especially the youth responded very positively after seeing the performance of the given technological interventions, and consequently started adopting weed management technologies in paddy, wheat, soybean, chick-pea and vegetable crops. Due to this the farmers were getting on an average 10-38% higher yield with an additional average profit of Rs.12000- 15000 per hectare. The success achieved in the cultivation of cereals has also changed the view of farmers about the overall agricultural practices. The farmers’ have also started growing vegetables in commercial scale from last couple of years. All these successes have created an environment of diversification in agriculture in this village. From a meagre 4-5 % prior to adoption, the level of weed management in crops using improved technologies increased to 85 % in the given village within a three year time span. There was a visible increase in the area under various crops. The outcome of the technological support gave a confidence and new ardour to them and they are now seriously occupied in agriculture.